(untitled) (Social Science Review, 2023)
Although Sufi-led political parties have been active in Bangladesh for almost four decades, they have received little scholarly attention. Therefore, this article discusses the historical context within which post-independence Sufi/Pir-centred political parties emerged, their interaction with other parties, and their electoral performance. It also touches upon some basic issues relating to Pir-cum political leaders: once a Pir becomes a politician, does his previous relationship with his murids (disciple) remain intact? This paper concludes that instead of posing any meaningful challenge to the political regimes, Pir-led parties have developed a tendency to maximise their political opportunities by reaching various kinds of agreements with dominant political parties. Social Science Review, Vol. 39(2), June 2022 [Special Issue] Page 59-78